PENGARUH KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. MITRA BETON MANDIRI PEKANBARU - Muhammad Wasfhah Muflih; Marzolina Marzolina; Arwinence Pramadewi (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
This study aims to determine the effect of organizational commitment and work discipline on employee performance with job satisfaction as an intervening variable. The population in this study included all permanent employees of the production department which amounted to 55 employees. Primary data were collected with questionnaires as an instrument to prove the results of the study, to test the hypothesis in this study was to use path analysis (path analysis) using the SPSS 26 for windows program. The sampling technique is carried out by means of a census, which is to make the entire population into a sample of 55 employees. The results of this study show that: 1) organizational commitment has a positive and significant effect on employee job satisfaction; 2) work discipline has a positive and significant effect on employee job satisfaction; 3) organizational commitment has a positive and significant effect on employee performance; 4) work discipline has a positive and significant effect on employee performance; 5) job satisfaction has a positive and significant effect on employee performance; 6) organizational commitment has a positive and insignificant effect on employee performance through job satisfaction as an intervening variable; 7) work discipline has a positive and insignificant effect on employee performance through job satisfaction as an intervening variable.